2021
DOI: 10.1186/s12903-021-01569-1
|View full text |Cite
|
Sign up to set email alerts
|

Key factors associated with oral health-related quality of life in Sri Lankan adolescents: a cross sectional study

Abstract: Background Oral Health Related Quality of Life (OHRQoL) measures have emerged as an important oral health outcome that is able to reveal the subjective burden of illness due to oral diseases. The association between sociodemographic and socioeconomic factors, clinical dental conditions and OHRQoL indicators has been investigated in adolescent populations across the world. The purpose of this study was to investigate key factors associated with oral health-related quality of life of Sri Lankan a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
2
4
0
1
Order By: Relevance
“…These results further support the notion that maintaining good oral hygiene practices can positively influence the OHRQoL. A recent study conducted in Sri Lanka [ 13 ] reported no significant correlation between OHRQoL and the oral hygiene index, specifically the OHI-S. This disparity in findings may be partially attributed to differences in age.…”
Section: Discussionsupporting
confidence: 81%
“…These results further support the notion that maintaining good oral hygiene practices can positively influence the OHRQoL. A recent study conducted in Sri Lanka [ 13 ] reported no significant correlation between OHRQoL and the oral hygiene index, specifically the OHI-S. This disparity in findings may be partially attributed to differences in age.…”
Section: Discussionsupporting
confidence: 81%
“…Recent research found significant and relevant associations between OHRQoL and oral health knowledge, practice, and self-rated oral health. 5 Studies have shown that age, low income, brushing once a day, and tooth decay are all associated with poor OHRQoL, 6 and more favorable oral health attitudes and behaviors lead to better oral health-related quality of life among medical students. 7 Socioeconomic disparities and poor oral health habits appear to be part of the major factors responsible for dental extractions.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of oral conditions such as dental caries and periodontal status on OHRQoL of Sri Lankan adolescents have been assessed previously, 22 the present study was the first to have assessed the impact of dental fluorosis on OHRQoL in adolescents. The prevalence of dental fluorosis was 52% and of those, 37% had experienced an oral impact.…”
Section: Discussionmentioning
confidence: 98%